COBALT INDUCTION ON BIOSYNTHESIS OF CYANOCOBALAMIN by Streptomyces olivaceus IFO 3409. - Kasanah, Noer; Tunjung Pratiwi, Silvia Utami (Indonesian Journal of Pharmacy, 2002)
The structure of cyanocobalamin containing an essensial cobalt is as part the compound. The aim of this study was to investigate the influence of cobalt on biosynthesis of cyanocobalamin done by Streptomyces olivaceus IFO 3409. This experiment was carried out by cultivating S. olivaceus in fermentation medium contained glucose 1,5%, pepton 1%, yeast extract 0,25%, trace mineral and each of medium was added cobalt 5, 10, 20 ppm. Cyanocobalamin synthesized by the cells was harvested on the last exponential phase. The amount of cyanocobalamin was analyzed by spectrophotometer. The results show that no cyanocobalamin was produced by S. olivaceus culture without kobalt or treated with 5 ppm cobalt on medium. However cyanocobalamin was produced if the culture medium was treated with 10 and 20 ppm cobalt respectively. It was concluded that cobalt induced on cyanocobalamin biosyntesis, therefore optimation of adding kobalt might be examined on getting maximal cyanocobalamin produced by Streptomyces olivaceus IFO 3409.Key words: cyanocobalamin, cobalt, Streptomyces olivaceus IFO 3409.